Gulf Cooperation Council (GCC) : Economic Prospects and Policy Challenges for the GCC Countries. (Policy Papers; Policy Paper ;, 2012)
The already sluggish global recovery has suffered new setbacks and uncertainty weighs heavily on prospects. The euro area crisis intensified in the first half of 2012 and growth has slowed across the globe, reflecting financial market tensions, extensive fiscal tightening in many countries, and high uncertainty about medium-term prospects. Activity is forecast to remain tepid and bumpy, with a further escalation of the euro-area crisis or a failure to avoid the 'fiscal cliff' in the United States entailing significant downside risk.